Being (Truly) Critical in Media and Communication Studies: Reflections of a Media Scholar Between Science and Politics - Nordenstreng, Kaarle (Javnost-The Public, 2016)
This article is based on the author's contribution to the 2014 EURICOM Colloquium with its call for “reflections about critique and its conditions of possibility in the academic field of media and communication studies”. The article intends to review the context and nature of critical media and communication studies, seen through the author's personal experience in national as well as international spheres. While the testimony is autobiographical, an attempt is made to contemplate career development from the outside unlike in conventional memoires. This article is a prelude to a reflective review of the author's professional and political life story, forthcoming as a book in Finnish. The introduction gives examples of the use of the term “critical” in the field of media and communication studies, followed by a review of different ways in which the critical concept is used in the literature of the field, leading to a reflection on the precarious relationship between the intellectual and the political. A personal testimony by the author then provides a case illustrating how a scholar becomes critical under the influence of philosophical, political and international factors. The discussion at the end offers some concluding reflections.